Pola Makan dengan Kadar Asam Urat pada Masyarakat di Puskesmas Baitussalam Aceh Besar - Sri Warnita; Syukriadi Syukriadi; Taufiq Karma (VitaMedica : Jurnal Rumpun Kesehatan Umum, 2026)
Unhealthy dietary patterns are usually associated with the consumption of purine-rich foods. These foods can increase blood uric acid levels because dietary purines are metabolized into uric acid. This study aims to examine the relationship between dietary patterns and uric acid levels among community members in Baitussalam Health Center, Aceh Besar. This research employed a quantitative, analytical-descriptive design and a cross-sectional method. The study consisted of individuals diagnosed with gout at Baitussalam Health Center. The population consisted of 453 patients. The sample was 81 patients selected using accidental sampling technique. The data were collected using a Food Frequency Questionnaire (FFQ. The uric acid levels were measured using an Auto-check device. Univariate and bivariate analyses were performed, with the Chi-square test used to determine the association between variables. The findings showed that 35 respondents with good dietary patterns (85.4%), 6 respondents had normal uric acid levels (14.6%) and 35 repsondent had abnormal levels (87.5). In contrast, among those with poor dietary patterns had bad dietary intake 40 respondents with 5 respondents (12.5%) had normal uric acid levels, while 35 respondents (87.5%) had abnormal level. Bivariate analysis revealed a p-value of 0.000 (p < 0.05), indicating that the alternative hypothesis (Ha) was accepted and the null hypothesis (Ho) was rejected. These results prove a significant relationship between dietary patterns and uric acid levels. This study recommends that community members improve their dietary habits by consuming low-purine foods such as fruits, green vegetables, eggs, low-fat milk, and carbohydrate sources (e.g., rice and potatoes). Increasing water consumption is highly recommended to help reduce uric acid levels.